Integrating Local and Indigenous Animal Genetic Resources for Food and Agriculture (LIAnGRFA) into global biodiversity governance: A technical policy brief for the Convention on Biological Diversity - Tiambo, Christian K.; Katee, Sally M.; Mugo, Cynthia (International Livestock Research Institute, 2025)
The conservation and sustainable use of Local and Indigenous Animal Genetic Resources for Food and Agriculture (LIAnGRFA) are critical to biodiversity conservation, food security, climate resilience, and rural livelihoods. These livestock breeds – shaped over centuries through natural selection and traditional knowledge – possess unique traits such as disease resistance, heat tolerance, and efficient feed conversion, which makes them vital for sustainable agriculture and ecosystem health. This paper examines existing policy gaps, inconsistencies in international governance frameworks, and financial barriers limiting the conservation and sustainable use of LIAnGRFA. It provides actionable policy recommendations to integrate LIAnGRFA into the Convention of Biological Diversity (CBD), National Biodiversity Strategies and Action Plans (NBSAPs), and financial mechanisms such as the Global Environment Facility (GEF) and Green Climate Fund (GCF).